Boosting Grade 2A Islamic Elementary Students' Motivation via Hybrid Learning at Sari Bumi Sidoarjo - Naaziyah, Zumrotun; Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of hybrid learning on student motivation, focusing on class 2A students across varying levels of academic achievement. Employing a qualitative approach with a phenomenological lens, data was gathered through observation, interviews, documentation, and questionnaires. Validity was ensured through technical triangulation. The findings reveal a significant increase in student motivation following the implementation of hybrid learning. Students demonstrated heightened enthusiasm, attentiveness, earnestness, and active engagement in discussions and internet-based research. These results underscore the potential of hybrid learning to enhance student motivation, thus suggesting its relevance for contemporary educational practices. Highlights : Hybrid learning fosters student motivation: The study showcases how hybrid learning positively impacts students' motivation, resulting in increased enthusiasm and active participation in the learning process. Phenomenological inquiry: Employing a qualitative phenomenological approach, the research delves into the subjective experiences of students, providing rich insights into their perceptions and behaviors within the hybrid learning environment. Implications for educational practice: The findings underscore the potential of hybrid learning as a strategy to enhance student engagement and academic achievement, suggesting its relevance for contemporary educational practices worldwide. Keywords: Hybrid learning, Student motivation, Phenomenological approach, Academic achievement, Qualitative research